Plan estratégico 2019-2023 para la empresa productora de pitahaya amarilla orgánica PROECOMANA S.A. de la ciudad de Calceta - Ayala Zambrano, Julissa Lorena (2019)
The objective of this research was to carry out a strategic plan for a company that will export organic yellow pitahaya to European markets, as Spain's first market. The Proecomana SA company, has the need that in the rural areas of Junín, Tosagua and Bolívar cantons, the farmers carry out production of yellow pitahaya through organic agriculture to be able to supply and cover the percentage of an unsatisfied demand to the aforementioned market, for which its mission and vision was to be developed with the focus group technique with the participation of the members of the company and researchers. Subsequently, an external study was carried out, developed with the PEST analysis technique through bibliographic search, and in turn the study of Porter's 5 forces, with the data collected, the respective “EFE matrix” and “MPC”; followed by this activity, the internal analysis was carried out applying the interview and the EFI matrix was carried out. Once the information was obtained, the long-term and subsequent objectives of the SWOT matrix were proposed, where the strategies were structured to take advantage of existing strengths and opportunities, which were focused on promoting the production of organic pitahaya, since the study reflected that this type of production was carried out in the studied area; in turn, the quantity of producers of this exotic fruit is scarce, and in turn the search for strategic alliances with foreign distributors to achieve market positioning; finally, an action plan was structured that will allow the company to achieve faithful compliance with the above.